PENERAPAN MODEL PEMBELAJARAN TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DENGAN MEDIA FILM DOKUMENTER UNTUK MENINGKATKAN NILAI-NILAI PATRIOTISME DAN HASIL BELAJAR IPS SISWA KELAS IX D SEMESTER GASAL SMP NEGERI 2 BATURETNO WONOGIRI TAHUN PELAJARAN 2015/2016 - Nuryasin, Taufiq; Agung S., Leo; Joebagio, Hermanu (Sebelas Maret University (UNS), 2014)
This research aims to know whether this implementation of students team achievement division (STAD) with documentary film can improve student’s patriotism and IPS learning achievement of class IXD SMP Negeri 2 Baturetno, Wonogiri. This research was classroom action research, consist of three cycles with planning stage, implementation, observation, and reflection. Subject of this research was class of IXD SMPN 2 Baturetno totally 26 students. Data was collected using observation, documentary, and test. Data were analyzed by data collection, data display, and conclusion. The result of the cycle I was in class IXD SMPN 2 Baturetno Kabupaten Wonogiri, 14 students (53,84%) and 6 students (23,08%) have a low patriotism, however there was 6 students (23,08%) have high patriotism. The students learning achievement of this class was 73,08, it was under of the KKM grade 75. From 26 students, 16 students (61,54%) passed KKM, with that result can conclude if the IPS learning achievement should improved because the persentage of classical passing grade in the first cycle was not appropriate with the expectation that was 80% off whole students class, then needed the next cycle that was cycle II. The result of cycle II showed that the student’s patriotism was belong to high category where showed from average of achievement learning was 69,33. Frequency of group distribution was 16 students (61,54%) was getting high and very high patriotism and also 10 students (38,46%) had medium patriotism. The students learning achievement was 79,62 with classical passing grade was 73,08%, with the result that persentage classical passing grade on cycle II was not appropriate with the expectation that was 80% off whole students class. The result of cycle III showed that most of students belong to high patriotism with details 22 students (84,62%) and at least just 4 students (15,38%) still belong to medium patriotism. The students learning achievement of class was 81,55and could passed KKM that was 75 where from 26 students, 22(84,62%) students passed KKM and conclude that percentage classical passing grade of students learning achievement in cycle III was appropiate with the expectation which more than 80% of whole students.